Variational Boundary Conditions for Molecular Dynamics Simulations of Solids at Low Temperature (Communications in Computational Physics, 2018)
Boundary conditions for molecular dynamics simulation of crystalline solids areconsidered with the objective of eliminating the reflection of phonons. A variational formalismis presented to construct boundary conditions that minimize total phonon reflection. Localboundary conditions that involve a few neighbors of the boundary atoms and limited numberof time steps are found using the variational formalism. Their effects are studied and comparedwith other boundary conditions such as truncated exact boundary conditions or by appendingborder atoms where artificial damping forces are applied. In general it is found that, with thesame cost or complexity, the variational boundary conditions perform much better than thetruncated exact boundary conditions or by appending border atoms with empirical dampingprofiles. Practical issues of implementation are discussed for real crystals. Application tobrittle fracture dynamics is illustrated.